2012
DOI: 10.1002/cplu.201200052
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Strontium Borohydrides: Synthesis, X‐ray Structures, Catalytic Polymerization of ε‐Caprolactone, and Density Functional Calculations

Abstract: In the last few years a number of research groups started significant activity in the exploration of the coordination and organometallic chemistry of the heavier alkaline-earth metals. [1] Most of this work is focused on calcium, [2] an inexpensive and non-toxic element present in significant amounts in the human body. Indeed, synthetic access to such large alkalineearth metal complexes is often limited by their kinetic lability with detrimental Schlenk-type equilibria. [3] Within this reserach not only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and f-element 5,13,15,19,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] chemistry. Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and f-element 5,13,15,19,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] chemistry. Both ligands have been extensively used in main group, 1-16 transition [16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Introductionmentioning
confidence: 99%
“…Calculation studies revealed that the negative charge is mainly localized on the carbene carbon atom of the ligand backbone and that the charge delocalization from carbon to nitrogen is less important. 6,14,16,20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] In this context, some very efficient rare-earth metal initiators ligated by {CH(PPh 2 NSiMe 3 ) 2 } − have been unveiled for polymerization reactions. Mostly six membered metallacycles (N-P-C-P-N-M) are formed by chelation of the two imine groups to the metal center, adopting a pseudo-boat conformation.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, yielded a product mixture with stoichiometric HBpin, including some unreacted 1, and a product mixture with one major L-containing species ( 31 P{ 1 H} NMR resonance: δ 22.8 ppm) if an excess of HBpin is used. As a previously used alternative pathway to an MgH species on a sterically demanding monomeric tris(pyrazolyl)methanide MgnBu complex [35] (10), N(1)-P(1)-C(1)101.55 (13), N(2)-P(2)-C(1) 104.52 (14), P(4)-C(2)-P(3) 125.13 (19), N(3)-P(3)-C(2) 100.99 (14), N(4)-P(4)-C(2) 104.70 (14). (13), N(2)-P(2)-C(1) 104.52 (14), P(4)-C(2)-P(3) 125.13 (19), N(3)-P(3)-C(2) 100.99 (14), N(4)-P(4)-C(2) 104.70 (14).…”
Section: Resultsmentioning
confidence: 99%
“…Methanediides show several bonding modes containing typically one or two coordinated metal centres [2][3][4][5][6][7][8]. Over the past years, several examples of alkaline earth metal complexes of substituted bis(phosphoranyl)methanides and -methanediides have been forthcoming [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that show several coordination types B-E, see Figure 1. Most common is a dimeric Most common is a dimeric structure (B) with central M2C2 four-membered ring and additional M-E coordination, and monomeric complexes (C) with an N,C,N′-chelating methanide ligand and additional donors coordinating to the metal centre.…”
Section: Introductionmentioning
confidence: 99%
“…The calcocene [Cp (SiMe3)2 2 Ca] reacts with oxygen to give a biradical [82w] . [Cp*Sr(μ‐BH 4 )(thf) 2 ] 2 with rarely found bridging BH 4 groups acts as an initiator in ring‐opening polymerization of cyclic esters [82k] . The Cp Me4 Mg‐alkynyls catalyze the methyl methacrylate polymerization [82l] .…”
Section: Cp’ (Cpr/indr/flur) Complexesmentioning
confidence: 99%